Analisis Penetapan Tekstur Tanah Dengan Metode Hidrometer Pada Tanah Di Kecamatan Galang - Zalwa, Cut Aura; Dio Bukhori; Firzy Putra Pratama; Abdullah Rasyid Nasution; Janwar Iradi Ginting; Made Arya Pastika (PUCUK : Jurnal Ilmu Tanaman, 2025)
Research on soil characteristics is essential Research on soil characteristics is very important to support sustainable land management and utilization, especially in agriculture. This study aims to determine the soil capacity in Galang District, Deli Serdang Regency. Soil samples were taken from three points in Galang District using a soil drill at a depth of 0–20 cm and 20–40 cm. Soil characterization was carried out by analyzing the texture class. Determination of the texture class was carried out using the hydrometer method, which allows for more accurate analysis of soil particle distribution. soil texture is classified as Clay. These results provide an important picture of the physical and chemical conditions of the soil in the area, which can be used as a basis for optimal land use management and planning.